THE ROLE OF STATE-OWNED ENTERPRISES IN THE BANKING SECTOR IN NATIONAL ECONOMIC RECOVERY DURING THE COVID-19 PANDEMIC - Raden Irna Afriani; Rika Kartika (International Journal of Economy, Education and Entrepreneurship, 2021)
Covid-19 has harmed a variety of industries around the world, including Indonesia. Due to widespread social limitations, especially in the economic sector. Countless businesses and unemployed people have been affected by the virus's virulence. As a result, the Indonesian government does not stand silent when it comes to dealing with this issue. The PEN (National Economic Recovery) initiative is meant to help the country's economy get back on track. Because the data used comes from official sources, this research is descriptive quantitative, which means it presents the data in a methodical and comprehensive manner. This study was carried out in the banking sector, which is held by SOEs. A literature review was utilized to gather information and knowledge, which included theories, models, and concepts, in order to gain secondary data. According to the findings of this study, PEN at HIMBHARA bank has been funneled into the credit sector, both in the UMKM sector and throughout all business sectors, as well as housing loans